A Systematic Review of Mechanical Pretreatment Techniques of Wood Biomass for Bioenergy - Giorgia Di Domenico; Elisa Cioccolo; Leonardo Bianchini; Rachele Venanzi; Andrea Colantoni; Rodolfo Picchio; Luca Cozzolino; Valerio Di Stefano (Energies, 2025)
Lignocellulosic biomass is an exciting renewable resource for producing sustainable biofuels, thanks to its abundance and low environmental impact. However, its intricate structure makes it tough for enzymes to break it down effectively. Only efficient pretreatment methods can solve these problems. Among these, mechanical pretreatment methods are particularly good for industry because they are easy to use, do not require chemicals, and make it easier to achieve biomass. This systematic review adhered to the PRISMA protocols and used text analysis with VOSviewer to examine 33 academic articles published between 2005 and 2025. It highlighted two main types of mechanical pretreatment: size reduction (which includes grinding, crushing, and shredding) and densification (like pelletizing and briquetting). The results show that mechanical pretreatment can significantly boost biofuel yields by increasing surface area, lowering crystallinity, and allowing better enzyme penetration. Energy consumption remains a major hurdle for the overall sustainability of biomass conversion processes. This research provides a comprehensive review of current mechanical techniques, detailing their operational settings and performance metrics while also offering suggestions for optimizing biomass conversion processes. By promoting the use of mechanical pretreatment in biofuel production systems, the findings align with the principles of a circular economy and contribute to the development of greener energy sources.